The Trichoptera of Panama. XVIII. Twelve first country records of macrocaddisflies (Insecta, Trichoptera) from the Republic of Panama - Armitage, Brian J.; Aguirre, Yusseff; González, Tomás A. Ríos; Blahnik, Roger J. (Zootaxa, 2022)
Herein we add twelve first country records to Panama’s macrocaddisfly fauna (Insecta: Trichoptera): Calamoceratidae—Banyallarga acutiterga (Denning & Hogue 1983); Glossosomatidae—Protoptila bicornuta Flint 1963 and Protoptila jolandae Holzenthal & Blahnik 2006; Helicopsychidae—Helicopsyche rentzi Denning & Blickle 1979; Hydropsychidae—Calosopsyche sandrae (Flint 1967) and Smicridea acuminata Flint 1974; Leptoceridae—Oecetis hastapulla Quinteiro & Holzenthal 2017; Philopotamidae—Chimarra angustipennis Banks 1903; Polycentropodidae—Polyplectropus exilis Chamorro-Lacayo & Holzenthal 2004; and Xiphocentronidae—Caenocentron immaculatum Flint 1991, Caenocentron lausus Schmid 1982, and Xiphocentron alcmeon Schmid 1982.